Sweat-responsive natural small-molecule-based co-assembled hydrogels: multifunctional properties, transdermal delivery, and potential for hyperhidrosis therapy - Mingping La; Jiamei Le; Chunxia Yin; Pan Cheng; Fen Ju; Xiaohong Zhu; Cui Li (Chemical Engineering Journal, 2026)

Associations of long-term exposure to PM2.5 and its constituents with children renal function: a national retrospective study in China - Siwen Yu; Chunxia Cui; Wei Wu; Lianlong Yu; Yiya Liu; Qijiong Zhu; Zhiqing Chen; Shangfeng Yang; Yi Lin; Jianxiong Hu; Guanhao He; Xiaomei Dong; et al. (Environmental Research, 2025)

Reconciled estimation of Antarctic ice sheet mass balance and contribution to global sea level change from 1996 to 2021 - Rongxing Li; Guojun Li; Gang Hai; Huan Xie; Yuan Cheng; Wei Chen; Xiangbin Cui; Minghu Ding; Chunchun Gao; Tong Hao; Changqing Ke; Chuanjin Li; et al. (Science China Earth Sciences, 2024)
The Antarctic Ice Sheet (AIS) has been losing ice mass and contributing to global sea level rise (GSLR). Given its mass that is enough to cause ∼58 m of GSLR, accurate estimation of mass balance trend is critical for AIS mass loss monitoring and sea level rise forecasting. Here, we present an improved approach to reconciled solutions of mass balance in AIS and its regions from multiple contributing solutions using the input-out, altimetric, and gravimetric methods. In comparison to previous methods, such as IMBIE 2018, this approach utilizes an adaptive data aggregation window to handle the heterogeneity of the contributing solutions, including the number of solutions, temporal distributions, uncertainties, and estimation techniques. We improved the regression-based method by using a two-step procedure that establishes ensembled solutions within each method (input-output, altimetry, or gravimetry) and then estimates the method-independent reconciled solutions. For the first time, 16 contributing solutions from 8 Chinese institutions are used to estimate the reconciled mass balance of AIS and its regions from 1996 to 2021. Our results show that AIS has lost a total ice mass of ∼3213±253 Gt during the period, an equivalent of ∼8.9±0.7 mm of GSLR. There is a sustained mass loss acceleration since 2006, from 88.1±3.6 Gt yr −1 during 1996–2005 to 130.7±8.4 Gt yr −1 during 2006–2013 and further to 157.0±9.0 Gt yr −1 during 2014–2021. The mass loss signal in the West Antarctica and Antarctic Peninsula is dominant and clearly presented in the reconciled estimation and contributing solutions, regardless of estimation methods used and fluctuation of surface mass balance. Uncertainty and challenges remain in mass balance estimation in East Antarctica. This reconciled estimation approach can be extended and applied for improved mass balance estimation in the Greenland Ice Sheet and mountain glacier regions.

Phenotypic and genetic effect of carotid intima-media thickness on the risk of stroke - Wenqiang Zhang; Jingwei Zhu; Xuan Wu; Tianle Feng; Wei Liao; Xuan Li; Jianci Chen; Li Zhang; Chenghan Xiao; Huijie Cui; Chao Yang; Peijing Yan; et al. (Human Genetics, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Multiomics analyses reveal dose-dependent effects of dicofol exposure on host metabolic homeostasis and the gut microbiota in mice - Shuilin Wei; Xi Ye; Hehua Lei; Zheng Cao; Chuan Chen; Cui Zhang; Li Zhang; Chunxia Chen; Xiaoxia Liu; Limin Zhang; Xiaoyu Chen (Chemosphere, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

The neuroprotective effects of peracetylated chitosan oligosaccharides against β-amyloid-induced cognitive deficits in rats - Cui Hao; Minmin Han; Wei Wang; Cheng Yang; Jigang Wang; Yunliang Guo; Tao Xu; Lijuan Zhang; Chunxia Li (Marine Life Science & Technology, 2023)

Global, regional, and national deaths, disability-adjusted life years, years lived with disability, and years of life lost for the global disease burden attributable to second-hand smoke, 1990–2019: A systematic analysis for the Global Burden of Disease Study - Chunxia Zhai; Dingtao Hu; Guanghui Yu; Wanqin Hu; Qiqun Zong; Ziye Yan; Yuhua Wang; Linlin Wang; Tingyu Zhang; Hongyu Sun; Ling Cai; Liangyu Cui; et al. (Science of The Total Environment, 2023)

Transferring a new Fusarium head blight resistance locus FhbRc1 from Roegneria ciliaris into wheat by developing alien translocation lines - Rongrong Song; Yifan Cheng; Mingxing Wen; Xinying Song; Tong Wang; Mengshuang Xia; Haojie Sun; Menghao Cheng; Huimin Cui; Chunxia Yuan; Xiaoxue Liu; Zongkuan Wang; et al. (Theoretical and Applied Genetics, 2023)

Seasonality and Sex-Biased Fluctuation of Birth Weight in Tibetan Populations - Yaoxi He; Jun Li; Tian Yue; Wangshan Zheng; Yongbo Guo; Hui Zhang; Li Chen; Chunxia Li; Hongyan Li; Chaoying Cui; Ouzhuluobu; Xuebin Qi; et al. (Phenomics, 2022)

A life support-based comprehensive treatment regimen dramatically lowers the in-hospital mortality of patients with fulminant myocarditis: a multiple center study - Sheng Li; Shengyong Xu; Chenze Li; Xiao Ran; Guanglin Cui; Mengying He; Kun Miao; Chunxia Zhao; Jiangtao Yan; Rutai Hui; Ning Zhou; Yan Wang; et al. (Science China Life Sciences, 2019)

Chinese society of cardiology expert consensus statement on the diagnosis and treatment of adult fulminant myocarditis - Daowen Wang; Sheng Li; Jiangang Jiang; Jiangtao Yan; Chunxia Zhao; Yan Wang; Yexin Ma; Hesong Zeng; Xiaomei Guo; Hong Wang; Jiarong Tang; Houjuan Zuo; et al. (Science China Life Sciences, 2019)

Miscanthus sp.: Genetic Diversity and Phylogeny in China - Chunxia Ge; Xiuming Liu; Shimin Liu; Jing Xu; Hongfei Li; Tengteng Cui; Yao Yao; Ming Chen; Weili Yu; Cuixia Chen (Plant Molecular Biology Reporter, 2017)

Effects of pH, initial Pb2+ concentration, and polyculture on lead remediation by three duckweed species - Jie Tang; Chunxia Chen; Lei Chen; Maurycy Daroch; Yan Cui (Environmental Science and Pollution Research, 2017)